Sports Retailinf in India: Opportunities, Constraints and Way Forward - Arpita Mukherjee (Indian Council for Research on International Economic Relations (ICRIER), 2010)
Sports retail is a small but fast growing segment of modern retail in India. Recently, the country has been hosting many international sports and this has given a boost to this sector. Many foreign and domestic corporate retailers have entered sports retail. Sports goods manufacturing is a focus area in the Foreign Trade Policy (2009-2014) and the government is taking a fresh look at the current foreign direct investment policy in retail. In the above context, this paper provides an overview of the sports retail sector in India. Specifically, it presents the different retail formats, consumer profile, retailers' supply chain and sourcing. It also examines the retail and sports policies and their implications for this segment of retail, analyses the barriers faced by this sector and suggests policy reforms. The study found that the policy of allowing 51 per cent FDI in the single-brand format has not benefited this sector. The FDI ban on multi-brand retail is not an entry barrier since foreign retailers can establish their presence in India through other routes. The study found that since this is a niche segment of retail, FDI would not have an adverse impact on traditional retailers. It concludes that government should allow 51 per cent FDI in multi-brand sports retail. This will increase sourcing from India, lead to diffusion of technology, proliferation of brands, investment in sports and sports promotion, among others.
Keywords: C83; L67; L81; L83; L88; 330; Retail; sports; government policy; trade; consumer survey; Sportartikel; Sportbekleidung; Außenhandel; Auslandsinvestition; Außenwirtschaftspolitik; Wirkungsanalyse; Indien